Factors associated with dental pain in toddlers detected using the dental discomfort questionnaire - Izabella Barbosa Fernandes; Patrícia Reis-Sá; Rafaela Lopes Gomes; Luciane Rezende Costa; Joana Ramos-Jorge; Maria Letícia Ramos-Jorge (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2018)
Background: Dental pain is one of the most common symptoms of untreated oral problems and exerts a strong impact on the well-being of children. Aims: The aim of this study was to evaluate the associated factors with dental pain in children aged 1–3 years using the Brazilian version of the Dental Discomfort Questionnaire (DDQ-B). Methods: A cross-sectional study was conducted in the city of Diamantina, Brazil. A total of 318 randomly selected children were submitted to an oral clinical examination for the evaluation of tooth injuries and dental caries (International Caries Detection and Assessment System, [ICDAS]). The caregivers of the children were asked to answer the DDQ-B as well as a questionnaire addressing demographic and socioeconomic aspects of the family. Statistical analysis was performed and involved the description of frequencies as well as Poisson hierarchical regression analysis. Results: Dental pain was associated with a household income less than the Brazilian minimum monthly wage (Prevalence ratios [PRs] = 1.33, 95% confidence interval [CI]: 1.07–1.66, P = 0.011) and dental caries in dentin – ICDAS codes 5 and 6 (PR = 1.48, 95% CI: 1.13–1.94, P = 0.004). Conclusions: Greater frequencies of dental pain were found in 1–3-year-old children from families with a low monthly income and dental caries with visible dentin with or without pulp involvement.